Dimeric SecA Couples the Preprotein Translocation in an Asymmetric Manner - Tang, Ying (Public Library of Science, 2011)
The Sec translocase mediates the post-translational translocation of a number of preproteins through the inner membrane in bacteria. In the initiatory translocation step, SecB targets the preprotein to the translocase by specific interaction with its receptor SecA. The latter is the ATPase of Sec translocase which mediates the post-translational translocation of preprotein through the protein-conducting channel SecYEG in the bacterial inner membrane. We examined the structures of Escherichia coli Sec intermediates in solution as visualized by negatively stained electron microscopy in order to probe the oligomeric states of SecA during this process. The symmetric interaction pattern between the SecA dimer and SecB becomes asymmetric in the presence of proOmpA, and one of the SecA protomers predominantly binds to SecB/proOmpA. Our results suggest that during preprotein translocation, the two SecA protomers are different in structure and may play different roles.